2005
DOI: 10.1370/afm.406
|View full text |Cite
|
Sign up to set email alerts
|

The Break-Even Point: When Medical Advances Are Less Important Than Improving the Fidelity With Which They Are Delivered

Abstract: Society invests billions of dollars in the development of new drugs and technologies but comparatively little in the fi delity of health care, that is, improving systems to ensure the delivery of care to all patients in need. Using mathematical arguments and a nomogram, we demonstrate that technological advances must yield dramatic, often unrealistic increases in effi cacy to do more good than could be accomplished by improving fi delity. In 2 examples (the development of antiplatelet agents and statins), we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(124 citation statements)
references
References 57 publications
(50 reference statements)
0
121
0
3
Order By: Relevance
“…27 There is little investment on effective approaches to delivering evidence-based public health and medical interventions. 28,29 In the United Kingdom, 83.9% of public and philanthropic funding goes to basic and clinical research, and 4.8% goes to health services research. 24,25 • Targets health needs that can be met by profitable, high-technology products.…”
Section: A New Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…27 There is little investment on effective approaches to delivering evidence-based public health and medical interventions. 28,29 In the United Kingdom, 83.9% of public and philanthropic funding goes to basic and clinical research, and 4.8% goes to health services research. 24,25 • Targets health needs that can be met by profitable, high-technology products.…”
Section: A New Modelmentioning
confidence: 99%
“…• non-biomedical forms of health research (within high-income countries 29 and internationally); • biomedical research on rare diseases within high-income countries (although in the USA, the lack of incentives to conduct research on rare diseases is addressed by the Orphan Drug Act); • international biomedical research to develop interventions that target health conditions mainly found in developing countries; • creating real access (availability, af- To some extent, funding for product development public-private partnerships addresses the problem of a lack of incentives to do research on neglected diseases. However, this is contingent upon continued public and philanthropic funding for such partnerships.…”
Section: Implications For Global Healthmentioning
confidence: 99%
“…In fact, bedside US represents a radical cultural innovation, other than technologic. Of course, human psychological resistances continue to be the actual issue in promptly effecting a complete implementation of bedside US [28], more than the economic barriers [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Comparative effectiveness research can help decrease the attractiveness of accretive innovations, which offer small incremental advantages, often to a small minority of patients at high cost. The incremental effectiveness of rosuvostatin offers far less benefit than the more effective use of existing generic statins to prevent heart disease, 4 and comparative effectiveness research makes it more likely we will not pay the incremental cost of this newer branded medication.…”
Section: Published Online January 18 2013mentioning
confidence: 99%